2020
DOI: 10.17796/1053-4625-44.6.12
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Condylar Fracture: A Case Treated with a Conservative Myofunctional Approach

Abstract: Mandibular condylar fractures in a growing child may cause long-term consequences. A conservative approach has been recommended to permit the remodelling of the condyles as well as to re-establishing the mandibular dynamics and oral functions. This case report presents a bilateral mandibular condylar fracture in an 11 years old girl treated with myofunctional appliances in combination with exercises. The successful results from this clinical case support a conservative approach when treating mandibular condyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…A non-invasive approach is highly recommended, as it less traumatic for the patient, remodels the mandibular condyle, and re-establishes mandibular dynamics [1,2]. This was supported by a clinical case reported by these authors, where an 11 year-old female patient, who had a traumatic bilateral mandibular condylar fracture, was treated with a myofunctional conservative approach, which rendered a satisfactory remodeling of the mandibular condyles and the temporomandibular joint (TMJ) on both sides, with a full recovery of the mandibular dynamics, no limitation for mouth opening, and no facial asymmetry [3]. However, longterm follow up reports are not commonly found in the scientific literature.…”
Section: Introductionmentioning
confidence: 54%
See 3 more Smart Citations
“…A non-invasive approach is highly recommended, as it less traumatic for the patient, remodels the mandibular condyle, and re-establishes mandibular dynamics [1,2]. This was supported by a clinical case reported by these authors, where an 11 year-old female patient, who had a traumatic bilateral mandibular condylar fracture, was treated with a myofunctional conservative approach, which rendered a satisfactory remodeling of the mandibular condyles and the temporomandibular joint (TMJ) on both sides, with a full recovery of the mandibular dynamics, no limitation for mouth opening, and no facial asymmetry [3]. However, longterm follow up reports are not commonly found in the scientific literature.…”
Section: Introductionmentioning
confidence: 54%
“…The results of the case presented here showed that the treatment produced satisfactory results in recovering the manibular dynamics with a normal oral function, which was stable in the long-term. In this way, the previous clinical case report describing the myofunctional treatment, [3] as well as this report presenting a ten-year follow up of the same clinical case, support the idea that a conservative approach to treat mandibular condylar fractures is a good alternative to treat mandibular condylar fractures, which leads to a full recovery of the condylar morphology, as well as a re-establishment of the oral functions [1]. Furthermore, functional exercises at an early stage of the treatment may help to recover the mandibular dynamics and oral functions [2].…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations